Phases of the traditional 505 test: between session and direction reliability - Clark, R.; De Ste Croix, M. B. A.; Hughes, J. D.; Read, P. J. (Movement & Sport Sciences - Science & Motricité, 2020)
Change of direction (COD) testing has commonly reported a single total time to quantify performance despite that tests are made up of a number of different phases. No investigation into these phases has been completed, therefore the aim of this study was to examine the reliability between sessions and directions of the different phases of a 505 test. Twenty-one male youth athletes performed the 505 test in both directions on three occasions. Differences between directions and sessions were determined via a T-test and Two-way ANOVA respectively and a significance threshold was set at P = 0.05. All strategy variables show acceptable relative and absolute reliability in both directions between sessions (ICC = 0.73-0.94; CV = 2.3-6.3%) apart from ground contact time (GCT) (ICC = 0.57-0.68; CV = 14.8-22.4%). Significant differences were identified between session one and three for entry time. Significant differences between directions for exit time on day two and for full approach, entry and GCT on day three. The non-dominant turning direction showed lower relative and absolute reliability between session for entry time (ICC = 0.73 vs 0.89; CV = 6.3 vs 3.7%) and GCT (ICC = 0.57 vs 0.68; CV = 14.8 vs 22.4%). Results indicate the phases of a 505 COD test have high relative and absolute reliability between sessions, although turning directions should be considered independently.